Aether a knowledge sharing application - Apacible, Marvin; Reyes, Maria Criselda; Villarante, Jay Ricky (2006)
The global demand for efficient sharing of information is growing with the rapidly developing technologies-the thrust of which is aimed at developing highly distributed and increasingly mobile computers. This creates an enormous challenge in coming up with fresh ideas on distributed applications. JavaSpaces technology circumvents the major problems of distributed applications such as latency, synchronization and partial failure. This is done by providing asynchronous communication between remote processes provided for by the Jini technology. Futhermore, JavaSpaces can be implemented on a wide array of platforms where Java Virtual Machine is installed. With its huge potential in developing distributed applications, it has become relevant in aiding further research on various fields such as Biology, Physics, Mathematics, Engineering and Social Sciences. The technology is thus needed to be introduced into the academe and be adapted according to its needs. One interesting application of the technology is its ability to be a persistent repository of information. Without the limitation of an unreliable database and with the added simplicity of its algorithm, the application supports a harmonious exchange of information between peers. It also makes it possible to update information and trackdown all the changes to a particular data.
Thesis (B.S. Computer Science)--University of the Philippines, Diliman.
Keywords: Distributed systems; Distributed databases; Electronic data processin -- Distributed processing; JavaSpaces technology; Aether (Computer program).